Diagnosis of Eimeria spp. in Capra ibex (local meriz goat) - Al-Bayati, Saad M; Al-Rekani, Adnan M; Hamed, Ahmed A (The Iraqi Journal of Veterinary Medicine, 2016)
Out of 77 of local meriz goats (Capra ibex), 29 (37.67%) were diagnosed as infected with coccidia. The infection percentage was 22.08% in kids less than six months of age as compared with older age (15.59%). A moderate diarrhea was the only clinical sign which was observed in three infected kids (3.9%). Six Eimeria (E.) species were diagnosed, they were E.alijevi, E.christenseni, E.caprovina, E.minasensis, E.megaembryonica, E.ninakohlyakimovae. E.megaembryonica was suggested to be a new species as it has a bigger embryonic mass which could be depended as a new parameter for coccidia classification. The germinal disk with two layers was very clear and observed in pre-sporulation Oocyst of most diagnosed species. The last three criteria are new in their mentioning. Also, Pot. Dichromate with 5% concentration is essential for follow-up of sporulation process to prevent of high bio - pollutants of fecal samples but without any effects upon biological features of isolated coccidia species.